1976
DOI: 10.1017/s004317450006656x
|View full text |Cite
|
Sign up to set email alerts
|

Role of pH on Metribuzin Dissipation in Field Soils

Abstract: Metribuzin [4-amino-6-tert-butyl-3-(methylthio)-as-triazine-5(4H)one] residue analysis of soil samples showed greater amounts of residue extractable at soil pH 6.7 than 4.6. Metribuzin leaching increased with increasing soil pH. Metribuzin disappearance from soil followed pseudo first-order kinetics. The half-life of metribuzin decreased as soil pH increased and increased at all soil pH levels as depth of sampling increased. The decreased activity and decreased rate of metribuzin dissipation at lower soil pH i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…Specifically, the amine group of the herbicide is eliminated upon reaction with alcohols and carboxylic groups of organic matter 35. On the other hand, positive correlations were observed between metribuzin dissipation and soil properties such as pH, organic carbon content and bioactivity 36, 37. These parameters are also correlated with each other, as an increase in the organic carbon content usually parallels soil bioactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the amine group of the herbicide is eliminated upon reaction with alcohols and carboxylic groups of organic matter 35. On the other hand, positive correlations were observed between metribuzin dissipation and soil properties such as pH, organic carbon content and bioactivity 36, 37. These parameters are also correlated with each other, as an increase in the organic carbon content usually parallels soil bioactivity.…”
Section: Resultsmentioning
confidence: 99%
“…In another study on metribuzin, a negative correlation between sorption and soil pH was demonstrated. At pH 6.7 the sorption was about twice as the sorption at pH 4.6 (Ladlie et al, 1976). However, the sensitivity to pH may not be equal for metribuzin and the metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…Other unidentified metabolites are detected in experiments using 14 C‐labeled metribuzin (Moorman and Harper, 1989; Locke et al, 1994). Total degradation of metribuzin to inorganic species (mineralization) is usually below 10% of the metribuzin applied (Ladlie et al, 1976; Locke et al, 1994; Mallawatantri et al, 1996) and the highest result measured is 20% within 90 d (Moorman and Harper, 1989). Thus, stable metabolites may accumulate in the soil.…”
mentioning
confidence: 99%
“…Applied either pre‐emergence or early post‐emergence, metribuzin is very effective against annual grasses and numerous broad‐leaved weeds. As the soil is a complex system, degradation and dissipation of herbicides (including metribuzin) may be influenced by many factors, such as pH (Ladlie et al. , 1976a,b), temperature, moisture (Zimdahl et al.…”
Section: Introductionmentioning
confidence: 99%